The importance of national parks in maintaining the habitat integrity and diversity of Odonata species in Amazonian streams - Brito, Joás Silva; Silva, Everton Cruz; Ferreira, Victor Rennan Santos; Bastos, Rafael Costa; Cruz, Gabriel Martins; Monteles, Josinete Sampaio; Lima, Adriana; Raseira, Marcelo; Brejão, Gabriel Lourenço [UNESP]; Barbosa Oliveira-Junior, José Max; Dias-Silva, Karina; Michelan, Thaisa Sala; et al. (Springer Nature, 2024)
Protected areas are hugely important for preserving freshwater systems, given their importance for the human well-being and aquatic diversity. Our main objective in the present study was to investigate the diversity of adult Odonata species in streams inside a national park, and in streams located outside this protected area, under different human interventions. We analyzed assemblages of Odonata from 28 streams (inside = 17 and outside = 11) in Itaituba municipality, in Pará state, Brazil. Our results indicated that only habitat integrity and Zygoptera species composition significantly differed between both categories. The lack of more significant results may indicate some degree of buffer influence of the area of the national park since the streams inside and outside its area are a very short distance. Therefore, this closeness may be enough to allow the dispersal of Anisoptera species, considered effective dispersers, and some tolerant species of Zygoptera. However, only the Zygoptera suborder presented species specialists in streams inside and outside the national park, and even though this may be explained through their physiological aspects, another explanation may be that the presence of the national park mitigates the negative influence of human activities. Implications for insect conservation We highlight the importance of full-protected areas in preserving the diversity of Odonata species, through the maintenance of habitat integrity and physical structure. However, there is a need for more studies conducted inside protected areas to address their effectiveness for the preservation of aquatic systems.
Keywords: Anisoptera; Bioindicators; Monitoring aquatic biota; Preserve aquatic diversity; Protected areas; Zygoptera